ECONOMIC VIEWS OF S. KUZNETS AND THE RECEPTION OF THE THEORY OF MEDIUM-TERM CYCLES IN THE POLITICAL ECONOMY NARRATIVE - A. I. Bolvachev; K. A. Kushnarev (Вестник университета)
On the example of four micro-plots, the key theses of the economic views of the Nobel laureate S. Kuznets have been revealed. The main papers of Kuznets and his supervisor – W. K. Mitchell have been analysed, the reception of methods used by S. Kuznets in the prospect of economic theory has been traced. The reception of the mechanics of S. Kuznets’ research in modern political economy theory, referring to the research of D. Acemoglu and J. Robinson has been considered. In Appendix to this paper, a brief analysis of the political interpretation of the S. Kuznets cycle theory, proposed by D. Acemoglu and J. Robinson has presented. The research presented in the article summarizes the experience of research on economic views of S. Kuznets and emphasizes the prospect of using the author’s experiential optics.